1911
DOI: 10.1021/ja02216a012
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Oxygen in Sea Water.

Abstract: GEh'EIL4t, PHYSICAL AKD INORGANIC. slowly collecting. ii7hatever the cause, hair-ever, the method advocated eliminates it; while in a11 other case5 this method gives the same result as the regula1 OSIC. In the next paper of this serieq will be considered the standardization of a tip, and the calculation, from the drop weight, of surface tension and the molecular weight; while in the succeeding ones, which will appear in the immediate future, will be presented the results already obtained with the fifty or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1933
1933
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The pioneering work towards answering this question is that of Whipple and Stefanik (1996), who considered the decay of longlived radionuclides and found that it would lead to loss of the most volatile species. It was followed by the studies of Wallis (1980) and Irvine et al (1980), who showed by simple calculations that liquid water could be obtained in the cores of comet nuclei.…”
Section: Heating Versus Coolingmentioning
confidence: 99%
“…The pioneering work towards answering this question is that of Whipple and Stefanik (1996), who considered the decay of longlived radionuclides and found that it would lead to loss of the most volatile species. It was followed by the studies of Wallis (1980) and Irvine et al (1980), who showed by simple calculations that liquid water could be obtained in the cores of comet nuclei.…”
Section: Heating Versus Coolingmentioning
confidence: 99%
“…Their equation and constants are provided below and are also referenced in the Aanderaa manual (Aanderaa Instruments, 2004 The various equations were compared assuming O 2 air content of 20.9% and a total pressure of 760 mm Hg. Results are presented in Figure 5 and show good agreement among Fox (1909) and Whipple and Whipple (1911);Perry (1973);Colt (1984);and Garcia and Gordon (1992) particularly for temperatures between 0 and 30 o C.…”
Section: Introductionmentioning
confidence: 69%
“…Oxygen solubility data for fresh and sea water based on work from Whipple and Whipple (1911) and Fox (1909) 4. Bunsen coefficients and other formulas to account for barometric pressure, water vapor pressure and depth for calculating the solubility of gases in fresh water as documented by Colt (1984).…”
Section: Introductionmentioning
confidence: 99%
“…Calculated equilibrium values of dissolved oxygen, extrapolated from the sea level data of Whipple and Whipple (1911) Except for photosynthesis, almost all oxygen transter to the water occurs at the air-water interface. Because oxygen diffuses very slowly in water (Hutchinson, 1957, p. 587) , winds, water turbulence, and currents play a major role in the aeration of a water body.…”
Section: Dissolved Oxygenmentioning
confidence: 99%